Chronic SARS-CoV-2, a Cause of Post-acute COVID-19 Sequelae (Long-COVID)? - O’Donnell, Jake S.; Chappell, Keith J. (Frontiers in Microbiology, 2021)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is the cause coronavirus disease 2019 (COVID-19). Most individuals recover from SARS-CoV-2 infection, however, many continue to experience a cluster of persistent symptoms for months following resolution of acute disease; a syndrome that has been named Long-COVID. While the biological cause, or causes, of Long-COVID have not yet been confirmed, the main proposals have centered around either virus-induced autoimmunity or virus-induced tissue dysfunction. However, an alternative suggestion that a latent chronic infection could be responsible for the symptoms of Long-COVID has received minimal attention despite recent findings that SARS-CoV-2 genetic material and infections are detected in some individuals months following resolution of respiratory disease. Here we discuss literature supporting the possibility that Long-COVID occurs as a result of chronic SARS-CoV-2 infections.